Analisis Penerapan Etika Bisnis Islam Pada Pedagang Di Pasar Tradisional Merlung - M Gladion Diego Hermika Putra; Arsa Arsa; Solichah Solichah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Islamic business ethics plays an important role for business people to guide their behavior so that they do not deviate from moral and spiritual elements in earning a living through buying and selling. Islamic business ethics has a function, namely that Islamic business ethics tries to find ways to reconcile and harmonize different interests in the business world. Islamic business ethics also play a role in society's ever-changing business awareness. One of the interesting markets to examine is the Merlung traditional market which has many traders selling at the market such as: meat traders, vegetable traders, fruit traders, household equipment traders, etc. This research aims to determine the business ethics of traders in the Merlung traditional market from the perspective of Islamic business ethics. This research is included in the type of qualitative research, data collection techniques were carried out using interview, observation and documentation methods. The results of the research show that the majority of traders in the Merlung traditional market apply Islamic business ethics in conducting business, although there are several aspects which traders in the Merlung traditional market do not pay attention to and apply them with certain goals and with several obstacles.